PENGARUH HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI ES TEH NUSANTARA CABANG CILEUNGSI - Patmawati Patmawati; Yudi Wibowo (Jurnal Ilmiah Global Education, 2023)
The problem in this study is how the effect of price and location on purchasing decisions at Es Teh Nusantara Cileungsi Branch. The purpose of this thesis research is to find out how the price and location influence purchasing decisions at Es Teh Nusantara Cileungsi Branch. The type of research used is quantitative approach research. The data collection technique used a questionnaire. The population in this study were consumers who came to Es Teh Nusantara Cileungsi Branch. The sample taken was 200 respondents. Based on the results of the research that has been done, there is a positive relationship between price and location on purchasing decisions. This can be seen in the hypothesis test where the results obtained on the price variable have a significant influence on purchasing decisions with a tcount of 7.961> t table 0.138, with a significance value (probability) of 0.000 which is smaller than 0.05, price has a significant influence on purchasing decisions, where the tcount is 3.795> t table 0.138, with a significance value (probability) of 0, 000 which is smaller than 0.05, while together price and location have a significant effect on purchasing decisions with the results obtained Fcount of 408.326 with a significance value of 0.000 smaller than the significant level of 0.05, meaning that the price and location variables have a major influence on consumer purchasing decisions at Es Teh Nusantara Cileungsi Branch.